Plant and Plant Associated Microflora: Potential Bioremediation Option of Indoor Air Pollutants - Gunasinghe, Y.H.K.I.S.; Rathnayake, I.V.N.; Deeyamulla, M.P. (Nepal Journal of Biotechnology, 2021)
Indoor air pollution is a significant problem today because the release of various contaminants into the indoor air has created a major health threat for humans occupying indoors. Volatile Organic Compounds (VOCs) are pollutants released into the environment and persist in the atmosphere due to its low boiling point values. Various types of indoor activities, sources, and exposure to outdoor environments enhance indoor VOCs. This poor indoor air quality leads to adverse negative impacts on the people in the indoor environment. Many physical and chemical methods have been developed to remove or decompose these compounds from indoors. However, those methods are interrupted by many environmental and other factors in the indoor atmosphere, thus limit the applications. Therefore, there is a global need to develop an effective, promising, economical, and environmentally friendly alternatives to the problem. The use of the plant and associated microflora significantly impact reducing the environmental VOC gases, inorganic gases, particulate matter, and other pollutants contained in the air. Placing potted plants in indoor environments not only helps to remove indoor air pollutants but also to boost the mood, productivity, concentration, and creativity of the occupants and reduces stress, fatigue, sore throat, and cold. Plants normally uptake air pollutants through the roots and leaves, then metabolize, sequestrate, and excrete them. Plant-associated microorganisms help to degrade, detoxify, or sequestrate the pollutants, the air remediation, and promote plant growth. Further studies on the plant varieties and microorganisms help develop eco-friendly and environmentally friendly indoor air purifying sources.